Role of nanomaterials as adsorbents in heavy metal ion removal from waste water: A review. (February 2020) - Wadhawan, Shweta; Jain, Ayushi; Nayyar, Jasamrit; Mehta, Surinder Kumar
Graphical abstract: Adsorption of heavy metal ions by various kinds of nanoparticles. Highlights: A holistic analysis of the synthesis and efficacy of nanosorbents towards the removal of selected heavy metal ions. Emphasis on the effect of functionalization on the properties of nanoadsorbents. Mechanistic details of adsorption process. Effects of various parameters on adsorption. Potential of nanomaterials in heavy metal ions elimination from wastewater in future. Abstract: This review presents a holistic analysis of the synthesis and efficacy of nanosorbents towards the waste water purification by the removal of selected heavy metal ions, with special emphasis on the effect of functionalization of nanoadsorbents on certain key properties such as surface area, separation and adsorption capacity. We have compiled enormous data based on the characteristic properties of nanomaterials and their selective affinity towards certain heavy metal ions. The experimental factors like pH, adsorbent dosage, contact time, temperature, initial ion concentration and ionic strength affecting metal ion removal have also been explored. Besides, the different adsorption kinetics and adsorption isotherm models are discussed with the help of various illustrations to have an insight into the adsorption procedure.